International management : managing in a diverse and dynamic global environment (McGraw-Hill Irwin, 2005)
Offers a modern perspective of international management rooted in a recognized framework. The framework follows the generally accepted course structure beginning with the macro-environment, then moves to the firm level, and concludes with the individual manager in the international setting.